2017
DOI: 10.1016/j.jaubas.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of fungi isolated from coastal regions of Red Sea, Jeddah, Saudi Arabia

Abstract: To isolate fungal communities from coastal areas of the Red Sea in Saudi Arabia and identify and classify them by molecular techniques. Samples were collected from the seaside of the Red Sea in Jeddah, Saudi Arabia during March 2012 and stored in sterile screw cap bottles for further analysis. Phenotypic and genotypic characterization of fungal isolates were done using standard techniques. Eight fungal genera including Aspergillus, Penicillium, Thielavia, Fusarium, Emericella, Cladosporium, Scytalidium and Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Previously, both fungal and bacteria species were found to degrade crude oil. Alwakeel (2017) reported that Aspergillus flavus and Aspergillus sterilized and inoculated with the cultured species and the media was allowed to incubate for 10-12 days to have a perfect culture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, both fungal and bacteria species were found to degrade crude oil. Alwakeel (2017) reported that Aspergillus flavus and Aspergillus sterilized and inoculated with the cultured species and the media was allowed to incubate for 10-12 days to have a perfect culture.…”
Section: Resultsmentioning
confidence: 99%
“…The Czapek media composed of 30 g l sucrose as a carbon source. Instead of using sucrose as carbon source, 4% petroleum was used to prepare petroleum oil-Czapekdox broth (Reyes-César et al, 2014;Pi et al, 2017).. (Hasan et al, 2014;Alwakeel , 2017).…”
Section: Preparation Of Degradation Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…They are easily isolated and grown in the lab which makes it safer for the marine environment. The extreme conditions of marine life have caused fungi to become stress-resistant by forming many useful secondary metabolites (Alwakeel, 2017). These metabolites are said to have important biological activities including antimicrobial, anticancer, antioxidants and even antidiabetic, which is one of the reasons fungi are becoming more popular in marine drug discovery research (Hasan et al, 2015).…”
Section: Common Microorganism Isolates In the Persian Gulf And Gulf Of Oman In Relation To The Red Seamentioning
confidence: 99%
“…[19] Demonstrated to isolate and identified the lignin degrading white rot fungi from wood decay sample by using plate assay method. [20] Investigated to screen a fungi P. chrysosporium, P.ostreatus, Auricularia auriculajudae, and Lentinus edodes by using Dimethylsuccinate (DMS) medium and the laccase activity was measured.…”
Section: Screening Of Laccase Productionmentioning
confidence: 99%